Effect of TiO\(_2\) anatase nanocrystallite on electrical properties of PPy/TiO\(_2\) nanocomposite - Duong, Huyen Ngoc; Nguyen, Thanh-Phuong; Nguyen, Tung Trong (Communications in Physics, 2018)
Polypyrrole/titanium dioxide nanocomposite (PPy/TiO2) was synthesized by in-situ chemical polymerization of pyrrole (Py) monomer in colloidal suspension of TiO2 anatase. TEM images show that TiO2 anatase nanoparticles with size of around 3–4 nm are randomly imbedded on the surface and inside of PPy grain. The random distribution of TiO2 anatase nanoparticle in PPy matrix form variety of p-n contact on the surface and inside of the materials. As expectation, the charge exchange between oxygen and the PPy affect the p-n depletion regions and then modify the electrical properties of PPy. Upon exposure to the open air the conductivity of the PPy/TiO2 nanocomposite exhibits an increase of about 20 folds much larger than that of neat PPy. The enhancement is accounted for the modification of in the surface conductance of PPy/TiO2 nanocomposite as a combination of the TiO2 coupling and oxygen interaction